2012
DOI: 10.1590/s0102-311x2012000700014
|View full text |Cite
|
Sign up to set email alerts
|

Violência física entre parceiros íntimos: um obstáculo ao início do acompanhamento da criança em unidades básicas de saúde do Rio de Janeiro, Brasil?

Abstract: O objetivo do trabalho foi avaliar se a violência física entre parceiros íntimos é um fator de risco para o início tardio do acompanhamento da criança em unidades básicas de saúde (UBS). Trata-se de um estudo transversal que incluiu 927 mães/bebês com até seis meses de vida, atendidos em 27 UBS no Município do Rio de Janeiro, Brasil. Ter ido pela primeira vez à UBS após 60 dias de vida foi considerado o desfecho de interesse. Interações entre violência física entre parceiros íntimos, trabalho materno e qualida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
4
0
6
Order By: Relevance
“…Physical violence against pregnant women appears to be closely related to poor quality of prenatal care, suggesting the need for more frequent follow-up and reinforcing the importance of care and guaranteed access for women that are victims of violence 14,26 . A similar study had already pointed to the risk relations between intimate partner physical abuse and follow-up of children in primary care units, highlighting that care mainly exercised by women themselves can be influenced by their level of autonomy and capacity to mobilize and manage the necessary resources 27 . Studies have shown that the harms caused by a conflictive family environment act in a vicious circle; all those living in the micro-social space suffer from such experiences and display worse health indicators as a result 28,29 .…”
Section: Discussionmentioning
confidence: 74%
“…Physical violence against pregnant women appears to be closely related to poor quality of prenatal care, suggesting the need for more frequent follow-up and reinforcing the importance of care and guaranteed access for women that are victims of violence 14,26 . A similar study had already pointed to the risk relations between intimate partner physical abuse and follow-up of children in primary care units, highlighting that care mainly exercised by women themselves can be influenced by their level of autonomy and capacity to mobilize and manage the necessary resources 27 . Studies have shown that the harms caused by a conflictive family environment act in a vicious circle; all those living in the micro-social space suffer from such experiences and display worse health indicators as a result 28,29 .…”
Section: Discussionmentioning
confidence: 74%
“…Regarding most of the notifications in children under one year, the data highlighted by the study are in accordance with the strategies of the Health Department for children's health. It is possible that early notification occurs before the first year of life, for being related to a higher frequency in maternal and child health services, considering that it is in this period that neonatal screening occurs, monitoring of growth and development, immunizations, health education to encourage breastfeeding among other activities that are important for the promotion, prevention and treatment of children's diseases (11) .…”
Section: Discussionmentioning
confidence: 99%
“…As shown in a previous study, mothers involved in violent relationships were less likely to attend health services for routine pediatric follow-up of their infants, thus hindering their uptake by studies conducted only in health services 34 . A more comprehensive picture of the situation would require population-based studies to include women that rarely or never attend UBS.…”
Section: Discussionmentioning
confidence: 89%